Poor Sanitation, Deaths, and Regional Inequality in Twentieth-Century Chile - Morales-Campos, D (Massachusetts Institute of Technology, 2025)
Although Chile experienced a rapid epidemiological transition, high mortality linked to waterborne diseases persisted. The prevention of gastrointestinal illnesses was expensive, so mortality rates varied across geographical areas. The public expenditure on sanitation was insufficient and distributed unevenly across Chile. Before the late 1960s, the probability of dying from diarrhea could be up to twelve times higher in rural areas than in urban regions, which were better equipped with sanitation infrastructure. © 2025 by the Massachusetts Institute of Technology and The Journal of Interdisciplinary History, Inc.